South Africa's Responses to Gross Violations of Human Rights in Libya, Sudan and Zimbabwe: An Explanation of the Contradictions - Islam, Mohammed Saif (Department of Social Development, 2021)
When South Africa made the transition to democracy in 1994, led by the charismatic Nelson Mandela, it proclaimed that it would make human rights a centrepiece of its foreign policy. The international community also expected South Africa to play a leading role in promoting human rights around the world, not least due to the country's own history of gross human rights violations during apartheid. However, in the last 20 years, South Africa's track record in protecting human rights has come under scrutiny. Scholars have accused South Africa of turning a blind eye to gross human rights violations, contradicting its stated commitment to human rights. South Africa's responses to gross human rights violations in Libya, Sudan and Zimbabwe have been particularly criticised. This dissertation analyses the scholarly explanations of South Africa's contradictory behaviour in order to identify the strongest explanations on a bilateral level and a multilateral level in the context of South Africa's membership of the United Nations Human Rights Council (UNHRC). Delving into the literature on South Africa's foreign policy behaviour, I argue that South Africa has indeed failed to live up its promise of standing up for human rights. The emphasis on human rights in the country's foreign policy has also diminished over time. Most importantly, I argue that the major explanations of South Africa's contradictory behaviour are solidarity with African, developing and anti-apartheid allies; deterioration of domestic human rights regime which inevitably affects human rights promotion abroad; and South Africa's desire to be a leading conflict mediator that precludes it from criticising gross human rights violators, although there remain questions over South Africa's neutrality as a mediator.